Fuzzy SSPO-separation Axioms and Fuzzy α-SSPO Compactness (European Journal of Pure and Applied Mathematics, 2024)
In this paper we will introduce the concept of new separation axioms named fuzzy SSPO-separation axioms by using the fuzzy strong semi preopen sets and we will also introduce and investigate properties of  (alpha)-SSPO compactness. We will define and investigate relation between fuzzy separation axioms, fuzzy pre-separation axioms and different forms of fuzzy continuous mappings. We will also investigate the existence of a countable base of fuzzy strong semi preopen sets, we will define the concept of SSPO separability, the concept of (alpha)-SSPO Lindelof sets and examine their properties. With the concept of fuzzy strong semi pre-continuity, SSPO-irresolute continuous mappings and other forms of fuzzy continuity, we will investigate the new concept of fuzzy compactness and its properties in regards to the mentioned mappings.